Applying Best Value Approach In Establishing Guideline For Edible Bird Nest Cleaning Process - Tan, Kok Hong (2022)
Since 2009, Malaysia has become the world's second-largest producer of edible bird nests (EBN), following only Indonesia. With an estimated consumption of 5,654 tonnes in 2019, China is the most significant export market for edible bird nests. However, only 32 of Malaysia's 250 registered Edible Bird Nest (EBN) firms were granted an export license to China. This research aims to establish an alternative approach and guideline of the Edible Bird Nest cleaning process to assist stakeholders in obtaining a relative quality cleaning process. This is a mixed-method approach with qualitative and quantitative analytical processes. The semi-structured interview guide included questionnaires on challenges and the performance matrix of the industry. Subsequently, a survey was developed to accumulate sufficient data for analysing the performance of various practitioners. A total of thirty questions were prepared for questionnaires based on the Best Value Approach (BVA) concepts. BVA participants were identified using a Likert scale based on BVA characteristics. Participants who receive a total score of fifteen (15) out of thirty (30) will be classified as BVA practitioners. A score of 14 or less will be classified as Non BVA. BVA organisations in this research may not follow BVA processes, but they do have BVA company characteristics. A case study of selected cleaning facilities was closely examined to validate the iii quality performance of the new improved cleaning process. A new enhanced cleaning method that can keep up to 19.09 per cent of nutrient concentration can preserve 50.25 per cent of crude protein, a 30 per cent increase in the likelihood of nutrients being maintained. The Best Value Approach (BVA) could narrow the gap between the top and lowest achievers from 10.8% to 3.6%. Practitioners of the BVA obtain a 15% improvement in work performance, according to the researchers. The implications of this research benefit not only the cleaning facilities but the entire ecosystem and supply chain. BVA has a greater impact on Small and Medium Enterprises (SMEs) as compared to larger and more established companies.